Analisis Preferensi Konsumen terhadap Keputusan Pembelian Pie Brownies di Kabupaten Subang - Veralianta Br Sebayang; Wien Kuntari; Ani Nuraeni; Faranita Ratih Ratih; Dwi Yuni Hastati; Dedelia (Journal of Integrated Agribusiness, 2026)
Consumer preferences form the degree of evaluation of the possibility of making purchasing decisions, while consumers are faced with the diffusion of product and provider decisions with different tendencies. The purpose of the study was to assess consumer preferences for the purchase of brownie pie with a case study on UMKM's souvenirs and souvenirs in Subang city. A total of 76 respondents were selected using a conjoint analysis approach. The results of the analysis show that the flavor attribute is considered the most important or most considered in the decision to purchase brownie pie, with a value of 34.35%. The size attribute ranked second with a value of 18.61%. Followed by the price attribute with a value of 16.15%. And the lowest is the texture attribute with a value of 4.76%. To increase the target market, the strategies needed are (1) focus on developing and highlighting sweetness as the main attraction of the product, (2) offer the product at an affordable price, ideally around Rp20,000, to attract price-sensitive consumers, (3) provide products in large sizes to meet consumer preferences, (4) consider using chocolate aroma as one of the product's attractions, (5) optimize the appearance of the product with a brownish color and crispy texture, (6) take advantage of social media (Instagram and TikTok) for promotion, because it is effective and interactive